CHILD, EDUCATION AND LOVE. CHILD FOCUSSED REFLECTIONS FROM AN IRANIAN PRACTITIONER - Estemadi, Sanaz (Society Register, 2017)
The following paper is dedicated to theories connecting children, their upbringing and their education with living and working praxis based on love and understanding of children. This is just the first of a series of updates about educational activities of Donya Children Research Institute, based in Tehran (Iran), that will occur as an ongoing feature in Society Register creating a window of communication between 'distant' lands, connected through common interest in children's wellbeing.